1989
DOI: 10.1007/bf00999341
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of extraneous movements to lumbar paraspinal muscle activity: Implications for EMG biofeedback training applications to low back pain patients

Abstract: Within recent years clinicians and researchers have applied paraspinal EMG biofeedback procedures during static and dynamic movement retraining of chronic low back pain patients. Most of these applications make use of surface electromyography, an approach complicated by the fact that the erector spinae muscles are deeply situated. This descriptive study reveals that extraneous movements, such as neck flexion and pelvic rotation, can elicit profound activity from percutaneously placed EMG electrodes while littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The functional level of each participant was determined according to the wrist and digit active extension range of motion, a measure that had been determined to predict improvement in UE function use in past biofeedback studies 15,16 and had adopted as an inclusion criterion for many subsequent CIMT studies. Those in the high functioning group demonstrated active wrist extension of at least 20 degrees and active extension of the metacarpophalangeal joints and interphalangeal joints of at least 10 degrees.…”
Section: Methodsmentioning
confidence: 99%
“…The functional level of each participant was determined according to the wrist and digit active extension range of motion, a measure that had been determined to predict improvement in UE function use in past biofeedback studies 15,16 and had adopted as an inclusion criterion for many subsequent CIMT studies. Those in the high functioning group demonstrated active wrist extension of at least 20 degrees and active extension of the metacarpophalangeal joints and interphalangeal joints of at least 10 degrees.…”
Section: Methodsmentioning
confidence: 99%
“…Reliability was assessed on the LM percentage thickness change data using the intraclass correlation coefficient (ICC). 39 The reliability of test-retest designs is best analyzed using 2-way ICC models 46 ; in this study, the reliability of an average of 3 trials, which has been shown to optimize the precision of estimates, 27 was used to assess interexaminer reliability (ICC 3,3 ). To determine whether the repeatability of image measurement could impact same-day interexaminer reliability estimates, a single examiner (D.M.D.)…”
Section: Methodsmentioning
confidence: 99%
“…First, participants were either in pain during testing and the direct effect of pain on muscle responses cannot be excluded, or second, recordings were made with surface electromyography (EMG), which makes it impossible to draw conclusions about activity of specific muscles. 10,11 Investigation of the response of specific paraspinal muscles, and their discrete fascicles, to trunk loading is important because paraspinal muscles do not contribute equally to the control of spinal motion nor are they uniformly affected by LBP. Within the paraspinal muscles, the lumbar multifidus contributes up to 2/3 of the stiffness at individual lumbar segments 12 and has a high cross-sectional area and a low fiber length-to-muscle length ratio, making it uniquely designed to generate high forces.…”
mentioning
confidence: 99%